Structure–activity relationships for α‐calcitonin gene‐related peptide. (December 2013) - Watkins, Harriet A; Rathbone, Dan L; Barwell, James; Hay, Debbie L; Poyner, David R
<x xml:space="preserve">Abstract</x> Calcitonin gene‐related peptide (CGRP) is a member of the calcitonin (CT) family of peptides. It is a widely distributed neuropeptide implicated in conditions such as neurogenic inflammation. With other members of the CT family, it shares an N‐terminal disulphide‐bonded ring which is essential for biological activity, an area of potential α‐helix, and a C‐terminal amide. CGRP binds to the calcitonin receptor‐like receptor (CLR) in complex with receptor activity‐modifying protein 1 (RAMP1), a member of the family B (or secretin‐like) GPCRs. It can also activate other CLR or calcitonin‐receptor/RAMP complexes. This 37 amino acid peptide comprises the N‐terminal ring that is required for receptor activation (residues 1–7); an α‐helix (residues 8–18), a region incorporating a β‐bend (residues 19–26) and the C‐terminal portion (residues 27–37), that is characterized by bends between residues 28–30 and 33–34. A few residues have been identified that seem to make major contributions to receptor binding and activation, with a larger number contributing either to minor interactions (which collectively may be significant), or to maintaining the conformation of the bound peptide. It is not clear if CGRP follows the pattern of other family B GPCRs in binding largely as an α‐helix. Linked Articles This article is part of a themed section on Neuropeptides. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2013.170.issue‐7